The Role of National Leadership with Pancasila Character in Optimizing the State Defend Awareness - Zurman, Afrizal; Widjayanto, Joni; Hipdizah (Advances in Social Sciences Research Journal, 2020)
The multidimensional crisis faced by the Indonesian today requires a national leadership with Pancasila character. The weakness of national leadership is realized to have implications on the weakening of state defend awareness. State defend awareness is one of the important capitals in national development and also in solving various problems of the nation. State defend awareness will be influenced by one of the national leadership qualities. Pancasila as the foundation of state and state philosophy should be a guide and a referral in the conduct of every national leadership practice. This research aims to explain the role of national leadership that has the Pancasila character in optimizing state defend awareness. This study uses a qualitative descriptive approach. The results showed that the role of national leadership that has Pancasila character in building a state defend awareness is as a guide for the community in achieving the objectives of the country. Secondly, as the builder of the moral force of society in implementing state defend in national’s life. Meanwhile, the third role is as an inspirational role model for society